Analysis of the Effect of Service Quality on Customer Loyalty with Customer Satisfaction as a Mediator at Kos X in Sidoarjo - Permatasari, Aini Intan (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
This study aims to test the effect of service quality on customer loyalty with the variable of customer satisfaction mediation at boarding house X in Sidoarjo. This study uses quantitative methods using SmartPLS for data processing. The number of respondents in this study was 122 boarding house tenants selected using the purposive sampling method. The results showed that service quality affects customer satisfaction, service quality affects customer loyalty, customer satisfaction affects customer loyalty, and customer satisfaction has an effect on mediating service quality on customer loyalty.